Camera Surveillance as a Measure of Counterterrorism? - Alois Stutzer; Michael Zehnder (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Camera surveillance has recently gained prominence in policy proposals on combating terrorism. We evaluate this instrument of counterterrorism as resting on the premise of a deterrence effect. Based on comparative arguments and previous evidence on crime, we expect camera surveillance to have a relatively smaller deterrent effect on terrorism than on other forms of crime. In particular, we emphasize opportunities for substitution (i.e., displacement effects), the interaction with media attention aspired to by terrorists, the limits of real-time interventions, the crowding-out of social surveillance, the risk of misguided profiling, and politico-economic concerns regarding the misuse of the technology.
Keywords: H56; K42; 330; Camera surveillance; closed-circuit television (CCTV); public security; deterrence; terrorism